Absorption, Metabolism, and Excretion, In Vitro Pharmacology, and Clinical Pharmacokinetics of Ozanimod, a Novel Sphingosine 1-Phosphate Receptor Modulator - Surapaneni, Sekhar; Yerramilli, Usha; Bai, April; Dalvie, Deepak; Brooks, Jennifer; Wang, Xiaomin; Selkirk, Julie V.; Yan, Yingzhuo Grace; Zhang, Peijin; Hargreaves, Richard; Kumar, Gondi; Palmisano, Maria; et al. (Drug metabolism and disposition, 2021)
Ozanimod is approved for the treatment of relapsing forms of multiple sclerosis. Absorption, metabolism, and excretion of ozanimod were investigated after a single oral dose of 1.0 mg [14C]ozanimod hydrochloride to six healthy subjects. In vitro experiments were conducted to understand the metabolic pathways and enzymes involved in the metabolism of ozanimod and its active metabolites. The total mean recovery of the administered radioactivity was ∼63%, with ∼26% and ∼37% recovered from urine and feces, respectively. Based on exposure, the major circulating components were active metabolite CC112273 and inactive metabolite RP101124, which together accounted for 50% of the circulating total radioactivity exposure, whereas ozanimod accounted for 6.7% of the total radioactive exposure. Ozanimod was extensively metabolized, with 14 metabolites identified, including two major active metabolites (CC112273 and CC1084037) and one major inactive metabolite (RP101124) in circulation. Ozanimod is metabolized by three primary pathways, including aldehyde dehydrogenase and alcohol dehydrogenase, cytochrome P450 isoforms 3A4 and 1A1, and reductive metabolism by gut microflora. The primary metabolite RP101075 is further metabolized to form major active metabolite CC112273 by monoamine oxidase B, which further undergoes reduction by carbonyl reductases to form CC1084037 or CYP2C8-mediated oxidation to form RP101509. CC1084037 is oxidized rapidly to form CC112273 by aldo-keto reductase 1C1/1C2 and/or 3β- and 11β-hydroxysteroid dehydrogenase, and this reversible oxidoreduction between two active metabolites favors CC112273. The ozanimod example illustrates the need for conducting timely radiolabeled human absorption, distribution, metabolism, and excretion studies for characterization of disproportionate metabolites and assessment of exposure coverage during drug development. Absorption, metabolism, and excretion of ozanimod were characterized in humans, and the enzymes involved in complex metabolism were elucidated. Disproportionate metabolites were identified, and the activity of these metabolites was determined.